Ultrasonographic appearance of supraspinatus and biceps tendinopathy improves in dogs treated with low-intensity extracorporeal shock wave therapy: a retrospective study - Kern, Tari; Manfredi, Jane; Tomlinson, Julia (Frontiers in Veterinary Science, 2023)
Objective: This study aimed to determine if dogs with shoulder tendinopathy diagnosed via musculoskeletal ultrasound would show improvement on imaging after treatment using piezoelectric shockwave therapy and rest. Methods: Medical records were reviewed for dogs diagnosed with biceps and/or supraspinatus tendinopathy via musculoskeletal ultrasound, treated using piezowave shockwave, and re-imaged post-treatment. Data collected included patient signalment, duration and grade of lameness, prior rest, piezowave dose, and patient outcome, including return to sport where applicable. Images were scored using an adapted ultrasound grading scale, in addition to obtaining cross-sectional area measurements. Statistics included: Shapiro-Wilks tests (normality), Wilcoxon matched pairs signed rank tests (pre-vs. post-treatment comparisons), and Spearman Correlation Coefficients (lameness grade versus ultrasound score) (significant at P<0.05). Results: Twenty-six of thirty dogs had pathology involving both the biceps and supraspinatus tendons in one limb, with twenty-seven of thirty having tendon/s affected bilaterally. For both tendons, post-treatment cross-sectional area and ultrasound score was significantly lower than pretreatment (P<0.001). Lameness decreased clinically (P<0.0001) following piezowave shockwave treatment regardless of the tendons involved, but lameness score did not correlate to ultrasound score for either tendon. Conclusions: Dogs with tendinopathy of the biceps brachii and supraspinatus showed significant improvement on follow-up musculoskeletal ultrasound and lameness evaluation after treatment of their tendons using piezoelectric shockwave therapy with rest.